Effect of Rosella Petal Extract (Hibiscus sabdariffa L.) On SOD Activity and Mouse Eye Rat (Rattus Wistar) Exposed to Gamma Radiation - Rara Pramita; Chomsin S. Widodo; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2014)
Measurement activity of superoxide dismutase (SOD) and Malondhyaldehyde (MDA) to analyze the effect of roselle calyx extract (Hibiscus sabdariffa L) after exposure 300 rad gamma radiation. 35 male white rats (Rattus Wistar) were exposed to fractination dose of 300 rad for 7 day, are given in the sonde 2cc/days roselle extract for 16 days with a dose variation 62.5 mg/200 g BW, 125 mg/200 g BW, 250 mg/200 g BW, 400 mg/200 g BW, and 550 mg/200 g BW. Measurement of the activity of SOD and MDA were done by thiobarbituric acid (TBA) methode. Extract Roselle (Hibiscus sabdariffa L) 250 mg/200 gr BW increase the activity of superoxide dismutase (SOD) and decrease Malondialdehyde (MDA) after being exposed to radiation of 300 rad.